Implementasi Brain Based Learning Dalam Mengasah Multiple Intelligences Di MTs Al-Qur’an La Raiba Hanifida Jombang - Risyunida Utami; Khoirotul Idawati (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2023)
Basically, every child is intelligent and has a tendency toward nine intelligences. To sharpen these intelligences, we need a learning model that optimizes brain activity. Brain-based learning is a learning model that involves the entire brain's potential as an approach to sharpening students multiple intelligences. The purpose of this research is to describe the concept of brain-based learning in the MTs al-Qur’an La Raiba Hanifida, the implementation of brain-based learning in multiple intelligences in the MTs, and the supportive and inhibitory factors of brain-based learning in multiple intelligences in the MTS and MA al-Qur'an La Raiba. In this study, the researchers used qualitative research and a case study approach. Data is collected using three techniques: (1) observation, (2) interviews, and (3) documentation. Data analysis techniques use domain analysis and taxonomic analysis. Data validation techniques use several things, including extending participation and triangulation. The result of this research is that: (1) The concept of brain-based learning in the MTs al-Qur’an La raiba is a learning model used as an approach in the learning process using the entire brain potential to maximize success. (2) Implementation of brain-based learning in sharpening multiple intelligences in the Hanifida MTs: planning, implementation, and evaluation 4) Factors supporting the implementation of brain-based learning in MTs and MA: training, support from the foundation, integration with the cottage, teachers (facilitators, providing support and guidance), availability of learning resources, and the ability of the student. The hindering factors are the difficulty in obtaining a valid reference for the age of MTs and MA students, taking a long time to upgrade the video, the recording device not meeting the desired specifications, internet problems, and changing the paradigm of teachers and students